The response to unfolded protein is involved in osmotolerance of Pichia pastoris - Dragosits, Martin (BioMed Central, 2010)
BACKGROUND: The effect of osmolarity on cellular physiology has been subject of investigation in many different species. High osmolarity is of importance for biotechnological production processes, where high cell densities and product titers are aspired. Several studies indicated that increased osmolarity of the growth medium can have a beneficial effect on recombinant protein production in different host organisms. Thus, the effect of osmolarity on the cellular physiology of Pichia pastoris, a prominent host for recombinant protein production, was studied in carbon limited chemostat cultures at different osmolarities. Transcriptome and proteome analyses were applied to assess differences upon growth at different osmolarities in both, a wild type strain and an antibody fragment expressing strain. While our main intention was to analyze the effect of different osmolarities on P. pastoris in general, this was complemented by studying it in context with recombinant protein production. RESULTS: In contrast to the model yeast Saccharomyces cerevisiae, the main osmolyte in P. pastoris was arabitol rather than glycerol, demonstrating differences in osmotic stress response as well as energy metabolism. 2D Fluorescence Difference Gel electrophoresis and microarray analysis were applied and demonstrated that processes such as protein folding, ribosome biogenesis and cell wall organization were affected by increased osmolarity. These data indicated that upon increased osmolarity less adaptations on both the transcript and protein level occurred in a P. pastoris strain, secreting the Fab fragment, compared with the wild type strain. No transcriptional activation of the high osmolarity glycerol (HOG) pathway was observed at steady state conditions. Furthermore, no change of the specific productivity of recombinant Fab was observed at increased osmolarity. CONCLUSION: These data point out that the physiological response to increased osmolarity is different to S. cerevisiae. Increased osmolarity resulted in an unfolded protein response (UPR) like response in P. pastoris and lead to pre-conditioning of the recombinant Fab producing strain of P. pastoris to growth at high osmolarity. The current data demonstrate a strong similarity of environmental stress response mechanisms and recombinant protein related stresses. Therefore, these results might be used in future strain and bioprocess engineering of this biotechnologically relevant yeast.